2004
DOI: 10.1093/molbev/msi047
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Duplicate Control Regions in the Mitochondrial Genomes of Metazoa: A Case Study with Australasian Ixodes Ticks

Abstract: To investigate the evolution pattern and phylogenetic utility of duplicate control regions (CRs) in mitochondrial (mt) genomes, we sequenced the entire mt genomes of three Ixodes species and part of the mt genomes of another 11 species. All the species from the Australasian lineage have duplicate CRs, whereas the other species have one CR. Sequence analyses indicate that the two CRs of the Australasian Ixodes ticks have evolved in concert in each species. In addition to the Australasian Ixodes ticks, species f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(119 citation statements)
references
References 37 publications
5
113
0
1
Order By: Relevance
“…The duplicates include identical partial Cyt b sequences that lack an initiation codon and that are therefore functionless, even though nonfunctional copies are expected to degenerate and disappear rapidly under the tandem duplication and random loss model (Moritz and Brown, 1986;Boore, 2000). These findings suggest that gene conversions have occurred multiple times and maintained two identical or nearly identical copies, in accordance with previous studies (Abbott et al, 2005;Shao et al, 2005a). Although the duplicated content in the Cyt b sequence in Phoebastria is different from Thalassarche, the duplication might have originated in a common ancestor of the two genera.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The duplicates include identical partial Cyt b sequences that lack an initiation codon and that are therefore functionless, even though nonfunctional copies are expected to degenerate and disappear rapidly under the tandem duplication and random loss model (Moritz and Brown, 1986;Boore, 2000). These findings suggest that gene conversions have occurred multiple times and maintained two identical or nearly identical copies, in accordance with previous studies (Abbott et al, 2005;Shao et al, 2005a). Although the duplicated content in the Cyt b sequence in Phoebastria is different from Thalassarche, the duplication might have originated in a common ancestor of the two genera.…”
Section: Resultssupporting
confidence: 88%
“…Gene conversion also appears to occur in duplicated mtDNA sequences. This is based on observations of mtDNAs containing two identical or nearly identical copies that are shared with sister species, and which are more similar to each other than to the other copy in a different species (Shao et al, 2005a). Sequence duplications in the mt genome frequently involve the control region (CR), which is associated with the initiation of transcription and mtDNA replication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in birds duplication has been reported in which one of the copies of the CR is a degenerate control region. Shao et al (Shao et al, 2005) suggested that the two CRs may evolve independently and that duplicate CRs may be useful markers at the genus or family level.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases several independent PCR amplification steps need to be performed and several clones need to be sequenced, making targeting of independent genes cumbersome and increasing the probability for sequencing errors. For tick systematics these basic approaches have been extensively used (Black and Piesman, 1994;Black et al 1997;Black and Roehrdanz, 1998;Klompen et al 2000;Shao et al 2004;Shao et al 2005;Klompen et al 2007). Next-generation sequencing has been used to sequence amplified nuclear and mitochondrial PCR products (Burger et al 2012;Burger et al 2013;Xiong et al 2013;Burger et al 2014).…”
Section: Introductionmentioning
confidence: 99%